DIGITAL ARCHIVING APPLICATION IN AND OUT LETTER - Salsa Dilah Cicilia Putri; Muhammad Khoiruddin Harahap (Jurnal Mantik, 2022)
The archive is a very important document in a company, the archive aims to store information and data on a company. In some companies, archives are carried out using a manual system which increases the risk of data theft, data corruption and data loss. So with that, the researcher created an application to design digital archiving with the waterfall method. This research was conducted to solve various kinds of problems that exist in a company. During researching the problem, the author has observed the existing problems (observations) and solved the problem by making an application for web-based incoming and outgoing mail archives. this is done so that archive management can be carried out efficiently and this application is very safe to use because the application already uses security features, where this feature can maintain data properly